Alterations in Selected Blood Parameters Associated with Type 2 Diabetes Mellitus: Perubahan Parameter Darah Tertentu yang Berhubungan dengan Diabetes Melitus Tipe 2 - Al-Shammari, Mohammed J.I. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Non-insulin-dependent diabetes mellitus (NIDDM), also known as type 2 diabetes, is associated with various physiological and biochemical changes in the blood. Understanding these changes is important for better disease management and prevention of complications. Aims of the Study: This study aimed to investigate certain physiological and biochemical changes in blood parameters among patients with non-insulin-dependent diabetes mellitus (NIDDM) and compare the results with a healthy control group. Methodology: The study included a total of 50 participants (men and women) aged between 20 and 70 years. They were divided into two groups: 30 diabetic patients (18 females and 12 males) and 20 healthy individuals (11 males and 9 females). Blood samples were analyzed to assess various hematological and biochemical parameters. Results: The findings revealed no significant differences in red blood cell count, total leukocyte count, and the percentages of neutrophils, lymphocytes, and eosinophils between the diabetic and control groups. However, a slight, non-significant increase in platelet count was noted in diabetic patients. A significant increase (p < 0.001) was observed in both total cholesterol and triglyceride levels in the diabetic group compared to the controls. Additionally, a statistically significant difference in age was found between diabetic patients and healthy individuals (p = 0.0007), suggesting age as a potential contributing factor in the development and progression of NIDDM. Conclusions: The study highlights the significant elevation of cholesterol and triglyceride levels in individuals with NIDDM and underscores the potential role of age in the onset and progression of the disease. Regular monitoring of these parameters may aid in better management of diabetic patients.Highlight : Diabetic patients had significantly higher cholesterol, triglyceride, FBS, and HbA1c levels. No notable differences in RBC, WBC, or platelet counts were found between groups. Monitoring biochemical markers is vital for diabetes management. Keywords : Type 2 Diabetes, Blood Parameters, Cholesterol, Triglycerides, Glycemic Control